Nanosponge Innovations: Revolutionizing Targeted Drug Delivery - Sneha R Jakaraddi; Dr. Chandrashekar C. Patil (Asian Journal of Pharmaceutical Research and Development, 2026)
Nanosponges emerge as sophisticated nanoporous platforms, engineered through crosslinking of polymers like cyclodextrins, ethylcellulose, and polyvinyl alcohol to form stable, three-dimensional matrices with submicron cavities ideal for entrapping diverse drug molecules. These structures excel in overcoming solubility barriers for BCS Class II/IV compounds, leveraging non-covalent interactions, hydrogen bonding, vander Waals forces, and inclusion complexesto achieve loading efficiencies up to 33%, while enabling pH-responsive, sustained release via polymer hydration and diffusion. Diverse fabrication techniques, including emulsion-solventdiffusion, ultrasound-assisted synthesis, microwave irradiation, and melt methods, offer flexibility in tuning porosity, particle size (<1 μm, optimal 200-300 nm for dermal routes), and zeta potential (>+30 mV for stability). Rigorous characterization employs DLS, SEM/TEM, FTIR, helium pycnometry for porosity, and UV spectroscopy for entrapment, confirming biocompatibility, thermal stability to 300°C, and self-sterilizing properties due to 0.25 μm pores. Broad applications encompass oncology (paclitaxel, doxorubicin), antifungals (itraconazole, voriconazole), and topicals, with marketed formulations like Tamodex 20 and Piroxicam-20 validating clinical translation. Advantages include cost-effectiveness, biodegradability, taste-masking, and reduced side effects, though limitations persist, burst release risks, exclusion of macromolecules >400 Da, and scale-up challenges. Future prospects focus on magnetic targeting, greener solvents, and hybrid systems for personalized medicine.